DIABETES MELLITUS IN TEACHING STAFF OF PESHAWAR UNIVERSITY - Majeed, Sajida; Shaheen, Rubina; Begum, Jamila; Khan, Mir Hassan (Journal of Ayub Medical College Abbottabad, 1995)
ABSTRACT: A survey of diabetes mellitus in teachers of Peshawar University was carried out during September, 1993 to February, 1994. A proforma was developed. Blood and urine samples were analysed. Out of 340 persons, eleven (3.2%) were found diabetic, in which four were newly diagnosed. The disease was more common in males as compared to females. Increased prevalence was observed in older subjects, thus showing correlation with age in both sexes. Family members of 40.3% patients were also victim of the same disease. The major complications of diabetes include hypertension, obesity, kidney damage and ischemic heart disease. Routine screening of population for diabetes is recommended.